2019
DOI: 10.1002/fsn3.968
|View full text |Cite
|
Sign up to set email alerts
|

6‐Gingerol, an active pungent component of ginger, inhibits L‐type Ca2+ current, contractility, and Ca2+ transients in isolated rat ventricular myocytes

Abstract: Ginger has been widely used as a flavor, food, and traditional medicine for centuries. 6‐Gingerol (6‐Gin) is the active components of ginger and offers some beneficial effects on cardiovascular diseases. Here, the effects of 6‐Gin on L‐type Ca 2+ current (I Ca‐L ), contractility, and the Ca 2+ transients of rat cardiomyocytes, were investigated via patch‐clamp technique and the Ion Optix system. The 6‐Gin decreased the I Ca‐L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…6‐gingerol ([6]‐GR), a major bioactive constituent of ginger, is the most abundant and pungent gingerol in ginger. It has many effective pharmacological effects, such as cardiotonic, anti‐angiogenesis, anti‐inflammatory, anti‐cancer, antipyretic and anti‐ageing . Notably, [6]‐GR is a novel angiotensin II receptor (AT1) antagonist and offers some beneficial effects on cardiovascular diseases .…”
Section: Introductionmentioning
confidence: 99%
“…6‐gingerol ([6]‐GR), a major bioactive constituent of ginger, is the most abundant and pungent gingerol in ginger. It has many effective pharmacological effects, such as cardiotonic, anti‐angiogenesis, anti‐inflammatory, anti‐cancer, antipyretic and anti‐ageing . Notably, [6]‐GR is a novel angiotensin II receptor (AT1) antagonist and offers some beneficial effects on cardiovascular diseases .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] [6]-gingerol (6-Gin) is one of the primary pungent constituents of ginger and has antipyretic and cardiotonic properties. [7][8][9][10] Its structural formula is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…[28] Thus, the suppression of TLR4/NF-B pathway prevents inflammation. [29][30][31] Our previous study [9] have indicated that the cardio-protective effects of 6-Gin may because of a decreasing of intracellular Ca 2+ via the inhibition of I Ca-L and contractility in rat cardiomyocytes. Herbal drugs, including 6-Gin are becoming more accepted among the public and medical professionals.…”
Section: Introductionmentioning
confidence: 99%
“…These researchers found that FG alleviated memory dysfunction induced by the Aβ 1−42 plaque toxicity and inhibited Aβ 1−42 plaque-induced neuronal cell loss in the CA3 region of the hippocampus. Thus, these studies showed the antiamnesic effects of FG against the Aβ 1−42 plaque toxicity by inhibiting neuronal cell loss and synaptic disturbance, besides suggesting that FG can alleviate AD-like memory dysfunction and neuronal degradation [ 36 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%